SOFTNESS TEST ST 300 SEBAGAI ALAT UJI KELEMASAN KULIT TERSAMAK PADA LABORATORIUM PENGUJIAN FISIS POLITEKNIK ATK - eko nuraini; Muhammad Ikhwan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2020)
The purpose of this research is to understand the working principle or operation of the Softness Leather Test equipment. Operation can use a variety of ring diameter variations in the test parameters. The test method in this study uses the ISO 17235: 2015 standard in principle of softnes testing, the skin is placed exactly in the position of the standard ring used, the lever is pressed at a certain speed on the skin area so that pressure arises which will produce a softness value of the sample. Tests used a ring diameter (ɸ) of 20 mm and 25 mm. Samples of working glove, Chrome tanned goat skin and vegetable tanned lining goat skin. Tests were carried out on the croupon area and body parts with three treatments, the test results data were average. The results obtained for the croupon area of ​​lining goat skin with ring diameter (ɸ) 20 mm, the thickness of the sample was 0.81, 1.8; diameter (ɸ) 25 mm is 2.16. The body part uses a ring diameter (ɸ) of 20 mm with a thickness of 0.84 of 1.66 and a diameter (ɸ) of 25 mm of 2.08. Samples of goat skin working glove tan Krom ring diameter (ɸ) 20 mm thickness of sample 0.63 parts of Croupon 4.7: ring diameter (ɸ) 25 mm was 5.6. The part of the ring body with a diameter (ɸ) of 20 mm with a thickness of 0.68 is 4.5; ring diameter (ɸ) 25 mm of 5.4. The skin with a higher thickness will give a smaller value to the softness leather test. The conclusion is that the raw material, production process, sample thickness, ring diameter, location of sample points have an effect on the results